Помогите!Пожалуйста!Умоляю!Срочно!

  • Так как   (а+в)²=а²+2ав+в²       (а-в)²=а²-2ав+в²     а²-в²=(а+в)(а-в)
    х²+2х+1   х²-2х+1    (х²-1)
    --------- +  ---------- -  -----------  =  1
        6              12               4
    2(х² +2х+1) + х²-2х+1 -3(х²-1)
    -----------------------------------------= 1
                     12
    2х²+4х+2+х²-2х+1-3х²+3
    --------------------------------- =1 сокращаем 2х²+х²-3х², а 4х-2х=2х
                 12
     2х+6            2(х+3)             х+3
    ------- = 1    ---------- = 1     -------- = 1      умножаем каждую часть на 6    х+3 = 6 
       12                12                   6                                     тогда х=6-3 = 3
                 
  • Общий знаменатель-12
    к первой дроби множитель-2,ко второй-1,к третьей-3,к единице-12
    2(x^2+2x+1)+x^2-2x+1-3(x^2-1)=12
    2x^2+4x+2+x^2-2x+1-3x^2+3=12
    2x=6
    x=3



See also: